2006
DOI: 10.1007/s00601-005-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

On Critical Stability of Three Quantum Charges Interacting Through Delta Potentials

Abstract: Abstract. We consider three one dimensional quantum, charged and spinless particles interacting through delta potentials. We derive sufficient conditions which guarantee the existence of at least one bound state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…It is rigorously proven that m/m 1 = 1 is the exact boundary, above which at least one bound state exists (as conjectured by [21]); the related conclusion is the existence of exactly One should discuss the connection of the present results with those, which take into account the finite interaction radius R e and (quasi)-1D geometry. The determination of the corrections due to finite interaction radius is not a trivial task, however, one expects that the corrections should be small for all calculated values provided R e /a and R e /a 1 are small, where a and a 1 are the two-body scattering lengths.…”
Section: Discussionmentioning
confidence: 55%
“…It is rigorously proven that m/m 1 = 1 is the exact boundary, above which at least one bound state exists (as conjectured by [21]); the related conclusion is the existence of exactly One should discuss the connection of the present results with those, which take into account the finite interaction radius R e and (quasi)-1D geometry. The determination of the corrections due to finite interaction radius is not a trivial task, however, one expects that the corrections should be small for all calculated values provided R e /a and R e /a 1 are small, where a and a 1 are the two-body scattering lengths.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, few analytical results were presented, in particular, it was shown that exactly one bound state of three equal-mass particles (m/m 1 = 1) exists for arbitrary λ 1 . Next, for two light fermions (in the limit of m/m 1 → 0) three particles are not bound for sufficiently large repulsive interaction between fermions, viz., for λ 1 /|λ| above the critical value ≈ 2.66735 [43], and exactly one bound state exists for λ 1 /|λ| below this value. To elucidate the general features of three one-dimensional particles, both numerical and analytical results were used to construct a schematic "phase" diagram, which shows the number of three-body bound states and a sign of the (2 + 1)-scattering length A in the plane of the parameters m/m 1 and λ 1 /|λ|.…”
Section: F One-dimensional Problemmentioning
confidence: 84%
“…Excitonic complexes in CNTs have been studied using many different approaches. 19,20,[48][49][50][51][52][53][54][55][56] In Ref. 19 it was demonstrated that the fractional dimensional model predicts the trion binding energy in CNTs with very high accuracy and therefore we use this as an example.…”
Section: Trions In Carbon Nanotubesmentioning
confidence: 99%